Las tareas de la adolescencia : una lectura de la adolescencia normal (2010)
ABSTRACT: In response to empirical research which criticizes the psychoanalytic position that attributes the character of "turmoil" to the normal adolescence, we propose a reading of some classical approaches on the subject. We approach to the adolescence not as a crisis but as a transition that has certain "psychological tasks" which are mobilized by body changes and social requirements. We grouped these tasks into three categories: to keep away of childhood internalized parental imago, being exposed to new environments relational and the reconstruction of the Self. In these tasks are grouped some psychoanalytic theories of adolescence from a perspective that explain the mental processes without focusing on turmoil phenomenology. Finally, this process allows the adolescent to answer the central questions that man made to get in adulthood: Whom will I love?, What do I do? and Who am I?